Critique from the Natural Form: Subsumption and Technological Rent - Torres Gaxiola, Andrea (2025)
This article analyzes Bolívar Echeverría’s theory of the natural form to present his critical proposal of capitalism. Initially, it aims to recover the concept of the natural form as a configuration of human life for reproduction. Subsequently, it examines the various dimensions of the process of subsuming the natural form into capitalism. Lastly, it investigates the theory of technological rent as the final stage of the subsumption of the social-natural form into the value form. The conclusion explores two potential resistance scenarios against capitalism that are derived from the analysis of the natural social form.